(untitled) - Medical Letter, Inc. (New Rochelle, N.Y., 2001)
Contents: drugs for rheumatoid arthritis, drugs for asthma, cancer chemotheraphy, drugs for cardiac arrhythmias, drugs for depression and anxiety, drugs for epilepsy,...
Keywords: Drug Interactions,Drug therapy,Pharmaceutical preparations